1991
DOI: 10.1038/bjc.1991.283
|View full text |Cite
|
Sign up to set email alerts
|

Perforin expression in lymphocytes infiltrated to human colorectal cancer

Abstract: al., 1985;Young et al., 1986a). PFP released from killer cells forms pores on the target cell membrane and induces cell lysis (Henkart, 1985;Zalman et al., 1986;Young et al., 1986b). Recent success in the cloning of PFP cDNA (Shinkai et al., 1988a;Lichtenheld et al., 1988;Lichtenheld & Podack, 1989;Lowrey et al., 1989) has allowed the examination of mRNA expression of PFP in killer cells. In the T cell lines, PFP gene expression was ascertained in the cytotoxic T lymphocytes (CTL) and natural killer (NK) cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 22 publications
2
8
0
Order By: Relevance
“…5 6 As Mulder et al find that the number of TCR + lymphocytes decreased in Dukes's A carcinomas, their results suggest that TCR t downregulation in TIL is a relatively early event in the interaction between a tumour and the immune system. In contrast, they describe an increase in the numbers of GrB expressing lymphocytes in the early stage of colorectal tumours, similar to earlier observations by Nakanishi et al 9 The authors infer that as the expression of this molecule involved in the cytolysis of tumour cells requires both TCR triggering and signalling via a costimulatory receptor some immune stimulation still takes place in Dukes's A carcinoma. In Dukes's D carcinomas, however, GrB expressing cells had disappeared from the tumour tissue, which can explain the lack of cytotoxic activity of TIL cells.…”
Section: Ignals From Lymphocytes In Colon Cancersupporting
confidence: 87%
“…5 6 As Mulder et al find that the number of TCR + lymphocytes decreased in Dukes's A carcinomas, their results suggest that TCR t downregulation in TIL is a relatively early event in the interaction between a tumour and the immune system. In contrast, they describe an increase in the numbers of GrB expressing lymphocytes in the early stage of colorectal tumours, similar to earlier observations by Nakanishi et al 9 The authors infer that as the expression of this molecule involved in the cytolysis of tumour cells requires both TCR triggering and signalling via a costimulatory receptor some immune stimulation still takes place in Dukes's A carcinoma. In Dukes's D carcinomas, however, GrB expressing cells had disappeared from the tumour tissue, which can explain the lack of cytotoxic activity of TIL cells.…”
Section: Ignals From Lymphocytes In Colon Cancersupporting
confidence: 87%
“…The factors driving the CD8 + T cell proliferation in colorectal carcinomas are not known but are likely to be the tumour cells themselves. As the CD8 + IEL are perforin negative [7], they may have a regulatory role, rather than a cytotoxic function. The CD4 + T cells also proliferate more when in contact with the tumour.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that in vitro , CD8 + T‐IEL are able to spontaneously lyse colon carcinoma cell lines [6]. Around 20% of the stromal, but almost none of the intraepithelial CD8 + T cells express perforin in Dukes’ A carcinomas, decreasing to just 3% in the stroma in Dukes’ C cases [7]. Carcinoma‐infiltrating Vδ1 + T cells also lyse colon carcinoma cell lines [8], recognizing MICA and MICB on the tumour cells [9], and it has been shown in mice that Vα14 + NK T cells lyse tumour cells [10].…”
Section: Introductionmentioning
confidence: 99%
“…T cells infiltrating along the invasive margin were also reported to be mainly CD45RO + memory/effector‐type T cells 10. Infiltrating T cells also included cytotoxic T cells (CTL) carrying cytoplasmic perforin granules 11. Our observations suggest an occurrence of host anti‐tumor immune responses in colorectal cancer that affects prognosis.…”
mentioning
confidence: 99%